A Coordinated Multi-study Analysis of the Longitudinal Association Between Handgrip Strength and Cognitive Function in Older Adults. (11th June 2019) - Zammit, Andrea R; Piccinin, Andrea M; Duggan, Emily C; Koval, Andriy; Clouston, Sean; Robitaille, Annie; Brown, Cassandra L; Handschuh, Philipp; Wu, Chenkai; Jarry, Valérie; Finkel, Deborah; Graham, Raquel B; et al.
Abstract: Objective: Handgrip strength, an indicator of overall muscle strength, has been found to be associated with slower rate of cognitive decline and decreased risk for cognitive impairment and dementia. However, evaluating the replicability of associations between aging-related changes in physical and cognitive functioning is challenging due to differences in study designs and analytical models. A multiple-study coordinated analysis approach was used to generate new longitudinal results based on comparable construct-level measurements and identical statistical models and to facilitate replication and research synthesis. Methods: We performed coordinated analysis on 9 cohort studies affiliated with the Integrative Analysis of Longitudinal Studies of Aging and Dementia (IALSA) research network. Bivariate linear mixed models were used to examine associations among individual differences in baseline level, rate of change, and occasion-specific variation across grip strength and indicators of cognitive function, including mental status, processing speed, attention and working memory, perceptual reasoning, verbal ability, and learning and memory. Results were summarized using meta-analysis. Results: After adjustment for covariates, we found an overall moderate association between change in grip strength and change in each cognitive domain for both males and females: Average correlation coefficient was 0.55 (95% CI = 0.44–0.56). We also found a high level of heterogeneity in this association across studies. Discussion: Meta-analytic results from nine longitudinal studies showed consistently positive associations between linear rates of change in grip strength and changes in cognitive functioning. Future work will benefit from the examination of individual patterns of change to understand the heterogeneity in rates of aging and health-related changes across physical and cognitive biomarkers.